Introduction and Rapid Spread of SARS-CoV-2 Omicron Variant and Dynamics of BA.1 and BA.1.1 Sublineages, Finland, December 2021 - Vauhkonen, Hanna; Nguyen, Phuoc Truong; Kant, Ravi; Plyusnin, Ilja; Erdin, Mert; Kurkela, Satu; Liimatainen, Hanna; Ikonen, Niina; Blomqvist, Soile; Liitsola, Kirsi; Lindh, Erika; Helve, Otto; et al. (Emerging infectious diseases, 2022)
Multiple introductions of SARS-COV-2 Omicron variant BA.1 and BA.1.1. lineages to Finland were detected in early December 2021. Within 3 weeks, Omicron overtook Delta as the most common variant in the capital region. Sequence analysis demonstrated the emergence and spread through community transmission of a large cluster of BA.1.1 virus.